Protein structural analysis of the HIV-1 Nef protein through principal component and network analysis - Mendoza, Mikaella A. (Animo Repository, 2022)
Human Immunodeficiency Virus (HIV) continues to be one of the most serious global public health concerns. Over the past 15 years, different drugs from various classes have been developed, yet none are regarded as functional cures. As a result, there is a need for new targets to combat HIV-1, such as regulating the Nef-SH3 interaction, as it is considered a significant target for HIV pathogenesis. Understanding the dynamics and functions of protein targets is a major consideration in drug development research. Assays are unable to provide molecular perspectives of drug targets, and accessible three-dimensional protein structures only offer a glimpse of receptor structure. Thus, to understand the protein-protein interaction mechanism, complex dynamics of Nef-SH3 must be analyzed to determine key residue interactions that play an important role in Nef function and SH3 binding. Nef-SH3 computational protein structure analysis combining PCA and network analysis can reveal important information regarding protein biomarkers linked to HIV, and pinpoint potential targets. To study important structural and functional residues and motions impacting functions and inhibiting Nef-SH3, computational protein structural analysis through principal component analysis (PCA) and network analysis were performed. Molecular dynamics (MD) simulations were used to discover essential dynamics of the Nef protein and key interactions with SH3. PCA was employed to obtain a systemic perspective of essential protein motions. Network analysis was conducted to identify functional residues in the protein. Lastly, virtual screening and interaction analysis were implemented to identify two natural product hits that could inhibit Nef-SH3 binding.